Relations of Borel Type for Generalizations of Exponential Series
We prove that the condition \(olimits_n = 1^ + ∞ ( nλ _n )^ - 1 < + ∞ \) is necessary and sufficient for the validity of the relation ln F(σ) ∼ ln μ(σ, F), σ → +∞, outside a certain set for every function from the class \(H_ + ( λ )= ^df _f H( λ,f